Enhancing Subjective Wellbeing in Older Individuals with Amnestic Mild Cognitive Impairment: A Randomized Trial of a Positive Psychology Intervention - Konstantina Tsiflikioti; Despoina Moraitou; Christos Pezirkianidis; Georgia Papantoniou; Maria Sofologi; Georgios A. Kougioumtzis; Magdalini Tsolaki (Behavioral Sciences, 2023)
Objectives: This pilot study aims to explore the potential of a positive psychology intervention (PPI) in enhancing the subjective well-being of older individuals with amnestic mild cognitive impairment (MCI), a precursor to dementia. Design and Setting: A randomized trial was conducted, initially recruiting 51 participants aged 65 and above from the Greek Association of Alzheimer’s Disease and Related Disorders in Thessaloniki, Greece. The study employed a control-experimental group setup. To ensure randomization, each participant was assigned a unique number, and a random number generator was used for group allocation. Participants: A total of 41 eligible participants with amnestic mild cognitive impairment (MCI) were included in the study after screening. Intervention: The intervention consisted of a 3-week positive psychology program (PPI) where the PERMA Profiler questionnaire was administered at three intervals: pre-intervention, post-intervention, and one month after completion. Main Outcome Measures: The subjective well-being of participants. Results: The analysis, conducted mainly through mixed-measures ANOVAs, supported the study’s hypotheses, revealing that the 3-week PPI led to increased PERMA model scores and overall well-being, which persisted even after one month. Conversely, non-participants experienced declines in most domains except for Positive Emotion and Meaning, which demonstrated improvement and recovery during follow-up. Conclusions: These findings suggest the potential of PPI in enhancing the subjective well-being of older adults with amnestic MCI, with implications for addressing dementia-related challenges. Further investigation is warranted to pinpoint PPI effects on MCI and tailor interventions for improved subjective well-being.